Enhancing Student Independence through the Integration of Learning with Artificial Intelligence Tools - Shelvy Verlina Dwi Rahayu; Fazhar Restu Fauzi; Arie Susanty (SEAMEO SEAMOLEC, 2023)
This academic paper examines the incorporation of artificial intelligence (AI) tools as an efficient method to enhance students' self-reliance in the learning process. The rapid advancement of information technology necessitates inventive approaches in education, where AI can be integrated to offer a more individualized and effective learning experience. The study devises instructional strategies that leverage AI technology to provide a more dynamic and flexible learning environment. Applying AI across various aspects can aid students in accessing content tailored to their unique learning styles, fostering captivating learning experiences. The paper also underscores AI's advantages in supplying immediate feedback, guiding students, and encouraging creativity. However, it is essential to consider ethical and privacy considerations alongside the integration of AI in educational settings. With a comprehensive understanding of the potential and challenges, the utilization of AI can play a pivotal role in cultivating student autonomy and advancing education in the digital age.